Lessons Learnt from an 11-year Experience with Lymphatic Surgery and a Systematic Review of Reported Complications: Technical Considerations to Reduce Morbidity - Ciudad, Pedro; Escandón, Joseph M.; Manrique, Oscar J.; Bustos, Valeria P. (Archives of Plastic Surgery, 2022)
Complications experienced during lymphatic surgery have not been ubiquitously reported, and little has been described regarding how to prevent them. We present a review of complications reported during the surgical management of lymphedema and our experience with technical considerations to reduce morbidity from lymphatic surgery. A comprehensive search across different databases was conducted through November 2020. Based on the complications identified, we discussed the best approach for reducing the incidence of complications during lymphatic surgery based on our experience. The most common complications reported following lymphovenous anastomosis were re-exploration of the anastomosis, venous reflux, and surgical site infection. The most common complications using groin vascularized lymph node transfer (VLNT), submental VLNT, lateral thoracic VLNT, and supraclavicular VLNT included delayed wound healing, seroma and hematoma formation, lymphatic fluid leakage, iatrogenic lymphedema, soft-tissue infection, venous congestion, marginal nerve pseudoparalysis, and partial flap loss. Regarding intra-abdominal lymph node flaps, incisional hernia, hematoma, lymphatic fluid leakage, and postoperative ileus were commonly reported. Following suction-assisted lipectomy, significant blood loss and transient paresthesia were frequently reported. The reported complications of excisional procedures included soft-tissue infections, seroma and hematoma formation, skin-graft loss, significant blood loss, and minor skin flap necrosis. Evidently, lymphedema continues to represent a challenging condition; however, thorough patient selection, compliance with physiotherapy, and an experienced surgeon with adequate understanding of the lymphatic system can help maximize the safety of lymphatic surgery.
Keywords: lymphedema; intraoperative complications; postoperative complications; surgical procedures; lymphatic vessels; lymph nodes